Measurement of the inelastic proton-proton cross section at s√=13s=13 TeV; Journal of High Energy Physics; Vol. 2018, iss. 7 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich (2018, 2018)
Title screen